6t+9-5t=-9

Simple and best practice solution for 6t+9-5t=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+9-5t=-9 equation:


Simplifying
6t + 9 + -5t = -9

Reorder the terms:
9 + 6t + -5t = -9

Combine like terms: 6t + -5t = 1t
9 + 1t = -9

Solving
9 + 1t = -9

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 1t = -9 + -9

Combine like terms: 9 + -9 = 0
0 + 1t = -9 + -9
1t = -9 + -9

Combine like terms: -9 + -9 = -18
1t = -18

Divide each side by '1'.
t = -18

Simplifying
t = -18

See similar equations:

| y=-x^2+18x-50 | | 3(11+6y)-8y=-7 | | -7(2x-4)+5(3x-4)-2=4-5 | | 2x(x)=64 | | (5/12x)=(5/6) | | 4x^2+4y^2-16x-4y+5=0 | | 4g+7=5g-7-g | | 1.25/8=x/12 | | (8x^4y^7)^2/3 | | (9/2x)=(3/4) | | (((23y)/42)-5)=(4-((6y)/7)) | | 4+5x+6x+7x+10= | | 4(-.5-y)+7y=-14 | | 5w-7=w+1 | | =4E+06x+1E+08 | | 3x-2=-3x | | 5x-15/2x-8 | | 4f-24+4f=-8-4 | | 8=d^2/3-1 | | 3x-4/10 | | x^2+64=x | | -6.4x=-4.8 | | 4c+8c=-54+3c | | -x+4x=-16+26x | | 24x+8=14x-6 | | cotx/sinx(secx-cosx)=1 | | 6=0.8*-4 | | 6(c-4)=48 | | 18-10x=-2 | | 8y=7x+8solvex | | 8-10x=-2 | | (2x^4-7x^3-5x+18)-(9x^3-7x+5)=0 |

Equations solver categories